The Pandemic of Disinformation - Francesco Pira (Lubelski Rocznik Pedagogiczny, 2022)
Introduction: The continuing pandemic crisis represents a factor of profound destabilization, because it has exacerbated the phenomena already in place. In particular, social distancing, physical immobility have definitively shifted the construction of public discourse on the network, thus, giving rise to what is called “platform society”, where it is the platforms that produce the social structures in which we live.